Effect of eyestalk ablation on moulting and growth in the penaeid shrimp Metapenaeus monoceros (Fabricius, 1798) - Venkitaraman, P R; Jayalakshmy, K V; Balasubramanian, T (Indian Journal of Fisheries, 2016)
Penaeid shrimps (Metapenaeus monoceros) of two different size ranges were subjected to eyestalk ablation both unilaterally and bilaterally. The unilateral eyestalk ablated (UEA) shrimps consumed 8.9 % (35-40 mm) and 29.9 % (65-70 mm) more food than control shrimps whereas bilateral eyestalk ablated (BEA) shrimps consumed 18.7% and 31.8% less than the control group in the two size ranges respectively. Growth was estimated as length and weight increments and significant variation (p<0.05) was observed. The moult rate and dry moult weight showed marked differences between the two groups. In BEA shrimps, dry weight of moult in every succeeding moult was found to decrease. In the larger size group, values of protein efficiency ratio (PER) were almost 50% of that of the lower size group regardless of level of ablation. The UEA shrimps exhibited better protein efficiency ratio. The production rate of UEA shrimps were two to three times more than that of the control, whereas BEA shrimps showed comparatively low production rate. The net growth efficiency also followed a trend similar to that of production in both size ranges. The results suggest that unilateral eyestalk ablation can be resorted to accelerate growth and conversion efficiency in M. monoceros.